THE EFFECTIVENESS OF STUDENTS’ ENGLISH LEARNING ONLINE IN COVID 19 PANDEMIC ERA (A STUDY CASE AT THE EIGHTH GRADE STUDENTS OF SMP SWASTA KELUARGA SIAMBATON NAPA MANDUAMAS) - RISNA WATI MUNTHE (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: This study aims to determine: 1. How is the effectiveness of students English learning online in Covid-19? 2.What are the effectiveness factors of students English learning onlinein Covid-19? This research is qualitative. Data collection techniques include: questionnaires, interviews and documentation. The subjects of this study were English teachers and eighth grade students of SMP Keluarga Siambaton Napa Manduamas. Data analysis techniques using data reduction, data display, drawing conclusions. The results showed that 1. The effectiveness of student learning in online learningis effective. This can be seen from the questions given by researchers in online learning. 2. That factor effectiveness of student learning in online learning are the teacher preparing the material to be delivered, network constraints, and still many students who do not have mobile phones. Keywords: Covid 19, Effectiveness, Online Learning